The inappropriate use of Ritalin® for university academic improvement (Research, Society and Development, 2023)
Introduction: Ritalin (Methylphenidate) is one of the most prescribed stimulants for the treatment of attention deficit hyperactivity disorder (ADHD), but it has become increasingly common to find it in colleges, pre-university courses, and even in large companies, as it earned the nickname “intelligence pill”. Since these substances have the ability to increase alertness and motivation, in addition to having antidepressant properties, they improve mood and cognition. But despite so many benefits, like any medication, Ritalin® also has its harms, such as causing dependence when used incorrectly and without professional supervision. Objective: To identify the use of this medication, to guide discussions and also assist in prevention strategies, thus explaining the main reasons for use, methods of acquisition and possible side effects. Materials and methods: To this end, the following electronic databases were carried out: Scientific Electronic Library Online (SCIELO), Google Scholar, and LILACS - Bireme (Latin American and Caribbean Literature in Health Sciences), with the year of publication between 2018 and 2023. Results: The results obtained from the search in the consulted databases resulted in 45 articles, of which 15 were pre-selected, and after reading them in full, 10 articles were defined to compose the study. Discussion: Most users ignore the risks of harm from the non-prescribed use of methylphenidate, and consider the substance relatively harmless and safe, reinforcing the current concern regarding the use of the drug in question by university students, especially without professional recommendations. Conclusion: The results obtained in this study converge to the observation that the university public is the target of the need for awareness, bringing to light the damage and risks that the irresponsible use of this medication can bring, both in the long and short term.